Neoliberalism and the Biophysical Environment 2: Theorising the Neoliberalisation of Nature - Castree, Noel (Geography Compass, 2010)
There now exists a significant body of theoretically informed empirical research into ‘neoliberal environments’. It comprises numerous studies which together explore the connections between neoliberal principles and policies, on the one side, and the biophysical world on the other. However, making sense of them is by no means straightforward, despite their common focus on neoliberal environments. It is currently left to readers of these studies to synthesise them into a wider, joined-up account of neoliberal environments. This and two companion articles aim for precisely this sort of broad and coherent understanding. The contribution of this second instalment is to present an overarching political economic theory of ‘neoliberal environments’. By synthesising concepts from the work of Karl Marx, Karl Polanyi and James O’Connor, this article presents a framework for thinking about how neoliberal policies relate to the biophysical world.
Keywords: MARX, Karl, 1818-1883; O'CONNOR, James; neoliberal environments

D/developments after the Meltdown - Hart, Gillian (Antipode, 2010)
Part of what makes the current conjuncture so extraordinary is the coincidence of the massive economic meltdown with the implosion of the neoconservative Project for a New American Century, and the reappearance of US liberal internationalism in the guise of “smart power” defined in terms of Diplomacy, Development, and Defence. This essay engages these challenges through a framework that distinguishes between “Development” as a post-war international project that emerged in the context of decolonization and the Cold War, and capitalist development as a dynamic and highly uneven process of creation and destruction. Closely attentive to what Gramsci calls “the relations of force at various levels”, my task in this essay is to suggest how the instabilities and constant redefinitions of official discourses and practices of Development since the 1940s shed light on the conditions in which we now find ourselves.
Keywords: GRAMSCI, Antonio, 1891-1937; US hegemony; United States; capitalism; capitalist crisis; development; economic development; essay (literary form); hegemony; militarism

Now and Then - Watts, Michael J. (Antipode, 2010)
Antipode was launched into the firmament of the 1970s. We might reflect upon how well the journal and its contributors fully appreciated the historical gravity and weight of what was surrounding the project to create “a radical journal of geography”. What sort of radicalism was on offer? The language was “social relevance” from “a radical (Left) political viewpoint”. In writing to celebrate Antipode's birthday, this time in another, and similar, firmament there is still the need to confront the challenge of radicalism and its meanings. Whether we agree with Perry Anderson that the last vestiges of the 1960s have been finally swept away, that the “fluent vision” of the Right has no equivalent on the Left and that embedded liberalism is now as remote as “Arian bishops”, where do radical alternatives stand in relation to the fractured hegemony of neoliberalism? At the very least the need for alternatives is more pressing than ever. David Harvey has proposed rethinking the idea of “the right to the city”. But what other rights might we rethink? I reflect upon this question by returning to the 1960s and 1970s and Marxist debates over the law, and by thinking about the possibilities offered by this Polanyian moment.
Keywords: ANDERSON, Perry; Magna Carta; Marxist philosophy; Polanyi moment; Polanyian moment; common law - history; commons; essay (literary form); law; law - political aspects; markets; radicalism; scholarly periodicals

Crisis, Continuity and Change: Neoliberalism, the Left and the Future of Capitalism - Castree, Noel (Antipode, 2010)
Abstract:  This essay's point of departure is the coincident economic and environmental “crises” of our time. I locate both in the dynamics of capital accumulation on a world-scale, drawing on the ideas of Marx, Karl Polanyi and James O’Connor. I ask whether the recent profusion of “crisis talk” in the public domain presents an opportunity for progressive new ideas to take hold now that “neoliberalism” has seemingly been de-legitimated. My answer is that a “post-neoliberal” future is probably a long way off. I make my case in two stages and at two geographical scales. First, I examine the British social formation as currently constituted and explain why even a leading neoliberal state is failing to reform its ways. Second, I then scale-up from the domestic level to international affairs. I examine cross-border emissions trading—arguably the policy tool for mitigating the very real prospects of significant climate change this century. The overall conclusion is this: even though the “first” and “second” contradictions of capital have manifested themselves together and at a global level, there are currently few prospects for systemic reform (never mind revolution) led by a new, twenty-first century “red-green” Left.
Keywords: Britain; European Union; climate change; economic crisis; emissions trading; environmental crisis; social formation

Is the Globalization Consensus Dead? - Wade, Robert (Antipode, 2010)
The development economist Dani Rodrik recently declared that “the globalization consensus is dead”. The claim has momentus implications, because this consensus has steered economic policy around the world for the past quarter century. It emanates from the heartland of neoclassical economics, and defines the central tasks of the Washington-based organizations which claim to speak for the world. This essay answers two main questions. First, is Rodrik's claim true, and by what measures of “consensus”? Second, to the extent that the consensus has substantially weakened, is the state returning to the heart of economic life, as Karl Polanyi might have predicted? The answers? First, the globalization consensus about desirable economic policy has weakened, though it is far from “dead”. Second, the western state is returning to the heart of economic life in response to the current global economic crisis, but will retreat soon after national economies recover—because unless the crisis becomes a second Great Depression, the norms of more free markets and more global economic integration will be politically challenged only at the margins. New rules of finance may be introduced, but with enough loopholes that by 2015 Wall Street and the City will operate in much the same way as in the recent pre-crisis past.
Keywords: Washington consensus; catch-up growth; financial crisis; globalization consensus; income distribution; pension funds; poverty

Fair Trade Banana Production in the Windward Islands: Local Survival and Global Resistance - Torgerson, Anna McLoughlin (Agriculture and Human Values, 2010)
Fair trade banana farming in the Windward Islands of the Caribbean has emerged since the late 1990s in response to a crisis. Rulings by the World Trade Organization ended a longstanding trade dispute between the US and the EU by eliminating a system of preferential access of Windward Island bananas to the UK market. What followed was a period of rapid decline in banana exports from these small islands and a widespread abandonment of banana cultivation. Those banana farmers who remain are now primarily fair trade producers. Fair trade banana production in the Windward Islands can thus be conceived as a survival strategy that farmers have developed in response to a particular instance of neoliberal globalization. The paper considers this response especially in the context of recent fieldwork on the island of St. Vincent. In light of contributions by several scholars who have drawn upon the work of Polanyi to understand both fair trade and resistance to neoliberalism, fair trade banana production in the Windward Islands appears significant not only as a local survival strategy, but also as part of a larger countermovement that resists neoliberal globalization.
Keywords: agriculture in international trade; economic development: agriculture; energy; environment; international trade organizations; micro analysis of farm firms, farm households, and farm input markets Q12; natural resources; other primary products; trade policy